Biological control of Bradysia matogrossensis (Diptera : Sciaridae) in mushroom cultivation with predatory mites - Prado Freire, Renata Angelica; de Moraes, Gilberto Jose; Silva, Edmilson Santos; Vaz, Alcione Cicera; de Campos Castilho, Raphael (Springer, 2007)
Larvae of Sciaridae flies (Diptera) cause considerable damage to the mushroom Agaricus blazei (Murrill) ss. Heinemann in Brazil. Brazilian growers have had considerable difficulties in controlling this pest. The objective of this work was to test the effect of the predatory Laelapidae mite Stratiolaelaps scimitus (Womersley) as a control agent of Bradysia matogrossensis (Lane) in cultures of A. blazei. The work corresponded to an evaluation of the efficiency of that predator when released in boxes containing each about 15 L of commercial mushroom compost naturally infested with the pest. The results showed a significant effect of that predator on the population of B. matogrossensis. The release of either 665 or 1330 S. scimitus per box significantly reduced the pest population to levels that, according to grower's experience, apparently could not cause considerable damage. The positive results obtained warrant the conduction of complementary studies to determine the lowest rates of the predator that could still produce acceptable levels of control.
Keywords: Biological control; predatory mite; fungus gnat; Stratiolaelaps scimitus; Hypoaspis miles